Students Mental Health Diagnostic Expert System Using DASS Analysis and Rule-Based Reasoning: A Proposal - Azami N.H.; Salleh F.H.M.; Radzi H.M.; Gorment N.Z.; Aziz A.I.A.; Nee Y.J. (Springer Science and Business Media Deutschland GmbH, 2024)
The emergence of coronavirus disease (COVID-19) in December 2019 has led to major economic and social disruption in the new decade of twenty-first century. People from all walks of life are aware of the severity of this COVID-19 pandemic and probably feeling exhausted from the anxiety of it all. It has also brought into focus the mental health of various affected populations including university students. They are known to be the vulnerable group who can be easily exposed to diverse mental health issues such as stress, anxiety, and depression. Hence, this mental health diagnostic expert system called Easy Psychology System is proposed to evaluate the condition of UNITEN student's mental health during COVID-19 pandemic using Depression, Anxiety and Stress Scale (DASS) analysis and Artificial Intelligence (AI) rule-based reasoning method. The goal of this paper is to identify the requirements needed to develop the system in a web-based application platform. A comparative study on existing similar psychology system is also presented. The design and architecture needed to develop the system is also discussed. A review analysis is done to gather the requirements to develop the system. The information gathered will help to develop the system accordingly. 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.